Inverted opal luminescent Ce-doped silica glasses - R. Scotti; C. Canevali; S. Polizzi; M. Bettinelli; A. Speghini; F. Morazzoni (International Journal of Photoenergy)
Inverted opal Ce-doped silica glasses (Ce : Si molar ratio 1 ⋅ 10−3 were prepared by a sol-gel method using opals of latex microspheres as templates. The rare earth is homogeneously dispersed in silica host matrix, as evidenced by the absence of segregated CeO2, instead present in monolithic Ce-doped SG with the same cerium content. This suggests that the nanometric dimensions of bridges and junctions of the host matrix in the inverted opal structures favor the RE distribution avoiding the possible segregation of CeO2.